Body Weight Response of Broiler Chicken Subjected to Post-hatched Fasting - M. R. Hakim; B. Syamsuriadi; S. Banong; W. Pakiding (Jurnal Ilmu dan Teknologi Peternakan, 2014)
The research aimed to assess body weight respons of broiler chickens with various body weights (BW) at hatch when subjected to post-hatched fasting and its subsequent impact on the final body weight. Two hundred and sixteen unsexed broiler chickens, strain Cobb aged 12 hours post-hatch, were randomly assigned into floor pen (six chicks per pen). The research was arranged in a 3 x 4 factorial arrangement according to completely randomized design with three replications for each treatment combination. The first factor was the BW at hatch, i.e. light (30.1±0.39g), medium ((33.3±0.44g), and heavy (33.3±0.44g). The second factor was the duration of post-hatched fasting, i.e. 24, 36, 48, and 60 h, respectively. All chickens were weighed at 12, 24, 36, 48, 60 and 72 h post hatch, then at 7 and 35 days of age. Data analysis indicated that the BW of chicken subjected to fasting at 48 to 60 h post-hatch decreased significantly at the rate of 8.6% and 12.5% of the initial body weight, respectively. However, this condition was not related to the initial body weight status of the chicken. Availability of feed after the fasting period was not sufficient to compensate retardation of body weight of the chicken subjected to fasting 48-60 h post-hatch.